Comparison of oxidative stress in ASA physical status I patients scheduled for minimally invasive surgery under balanced or intravenous anesthesia - Braz, Mariana Gobbo [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Pierine, D. T. [UNESP]; Corrêa, Camila Renata [UNESP]; Ferreira, A. L. [UNESP]; Carvalho, L. R. [UNESP]; Yeum, K. J.; Salvadori, D. M. [UNESP] (Edizioni Minerva Medica, 2013)
Background. The effects of anesthetics on inflammation and oxidative parameters, evaluated in patients without morbidities undergoing undergoing minor surgery, remain unknown. The present study aimed to investigate the inflammatory and oxidative stress status in adult patients undergoing elective minimally invasive surgery, using different anesthetic techniques.Methods. Thirty patients classified as ASA physical status I, who were scheduled for minor surgeries (tympanoplasty or septoplasty), were randomly allocated into two groups: balanced (BAL) anesthesia maintained with isoflurane or total intravenous anesthesia (TIVA) with propofol. Blood samples were drawn prior to the induction of anesthesia (baseline), 120 mm after the beginning of anesthesia and one day after surgery. The proinflammatory cytokine IL-6 was determined by flow cytometry; DNA oxidation was evaluated by the single cell gel electrophoresis assay, and plasma malondialdehyde (lipid peroxidation biomarker) and antioxidant status were determined through fluorometry.Results. Increased IL-6 was observed one day after surgery in both groups (P=0.0001). Malondialdehyde levels did not change among the time points assessed or between the groups (P>0.05). Whereas BAL anesthesia had no effect on acid nucleic and antioxidant status, TIVA decreased oxidized/alkylated purines (P=0.03) and increased antioxidant status (P=0.002) during anesthesia. The two groups did not differ significantly in DNA oxidation or antioxidant status (P>0.05).Conclusion. BAL anesthesia maintained with isoflurane and TIVA maintained with propofol are safe by virtue of not causing oxidative stress status in ASA physical status I patients undergoing minimally invasive surgeries. Moreover, even in minor surgeries, TIVA with propofol produces an antioxidant effect in patients.
Keywords: Anesthetics; General surgery; Inflammation; Antioxidant agents